2021
DOI: 10.1177/15333175211021712
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Serum miRNAs in Alzheimer’s Disease

Abstract: This paper was aimed to analyze the microRNA (miRNA) signatures in Alzheimer disease (AD) and find the significant expressions of miRNAs, their target genes, the functional enrichment analysis of the confirmed genes, and potential drug treatment. The miRNA expression information of the gene expression profile data was downloaded from the Gene Expression Omnibus database. The total data sample size is 1309, including 1021 AD samples and 288 normal samples. A total of 21 differentially expressed miRNAs were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 51 publications
0
19
0
1
Order By: Relevance
“…One hundred and fifty-three articles were excluded for irrelevance. The full texts of the remaining 34 articles were evaluated, and 20 more articles were also excluded because they did not validate the components of the ceRNA loop using molecular techniques ( Wang et al, 2017 ; Yu et al, 2018 ; Zhou et al, 2019 ; Ma et al, 2020 ; Xu and Jia, 2020 ; Huaying et al, 2021 ; Lu et al, 2021 ; Ou et al, 2021 ; Tang et al, 2021 ; Zhang et al, 2021 ) and did not use human specimens or cell lines ( Jiang et al, 2016 ; Cai et al, 2017 ; Wang J. et al, 2018 ; Wang X. et al, 2018 ; Ma P. et al, 2019 ; Zhao et al, 2019 ; Li L. et al, 2020 ; Li X. et al, 2020 ; Yue et al, 2020 ; Zhou et al, 2020 ). Lastly, a total of 14 eligible articles remained ( Faghihi et al, 2010 ; Ke et al, 2019 ; Wang et al, 2019 ; Zeng et al, 2019 ; Zhu et al, 2019 ; Gao et al, 2020 ; Ge et al, 2020 ; Gu et al, 2020 , 2021 ; He W. et al, 2020 ; Yan et al, 2020 ; Yue et al, 2020 ; Fan et al, 2021 ; Zhang and Wang, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…One hundred and fifty-three articles were excluded for irrelevance. The full texts of the remaining 34 articles were evaluated, and 20 more articles were also excluded because they did not validate the components of the ceRNA loop using molecular techniques ( Wang et al, 2017 ; Yu et al, 2018 ; Zhou et al, 2019 ; Ma et al, 2020 ; Xu and Jia, 2020 ; Huaying et al, 2021 ; Lu et al, 2021 ; Ou et al, 2021 ; Tang et al, 2021 ; Zhang et al, 2021 ) and did not use human specimens or cell lines ( Jiang et al, 2016 ; Cai et al, 2017 ; Wang J. et al, 2018 ; Wang X. et al, 2018 ; Ma P. et al, 2019 ; Zhao et al, 2019 ; Li L. et al, 2020 ; Li X. et al, 2020 ; Yue et al, 2020 ; Zhou et al, 2020 ). Lastly, a total of 14 eligible articles remained ( Faghihi et al, 2010 ; Ke et al, 2019 ; Wang et al, 2019 ; Zeng et al, 2019 ; Zhu et al, 2019 ; Gao et al, 2020 ; Ge et al, 2020 ; Gu et al, 2020 , 2021 ; He W. et al, 2020 ; Yan et al, 2020 ; Yue et al, 2020 ; Fan et al, 2021 ; Zhang and Wang, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, nine groups of ceRNA networks were identified, including mmu_circ_0000331/miR-1224-3p/Unc13c, mmu_circ_0000400/miR-5120/Unc13c, mmu_circ_0000331/miR-5134-5p/Unc13c, mmu_circ_ 0000331/miR-1224-3p/Tbx20, mmu_circ_0000400/ miR-504-3p/Tbx20; mmu_circ_0000331/miR-5134-5p/Tbx20, mmu_circ_0000406/miR-24-3p/St8sia2, mmu_circ_0000400/miR-6396/St8sia2, and mmu_circ_ 0000798/miR-672-5p/St8sia2. Through literature review of each circRNA and miRNA, miR-24-3p was found to be closely related to AD [53][54][55]. Among them, miR-24-3p in Liu et al's study was noted to be negatively correlated with the score of mild mental state testing of AD, and down-regulation of miR-24-3p could promote cell proliferation and inhibit cell apoptosis [56].…”
Section: Discussionmentioning
confidence: 99%
“…A downregulation in miR-30b-5p levels (downregulated in MNR) was observed in patients with BD in comparison to healthy controls [53]. Finally, miR-6747-3p (upregulated in MNR) was found to be upregulated in the serum of Alzheimer's disease patients compared to healthy controls [54].…”
Section: Mirnas Previously Associated With Psychiatric Conditionsmentioning
confidence: 89%